Temporal trends and spatial variations of chlorinated paraffins and olefins in sewage sludge from eight Swiss wastewater treatment plants from 1993 to 2020 - Jules Hutter; Oscar Mendo Diaz; Marco Knobloch; Markus Zennegg; Jean Claude Vogel; Edith Durisch; Urs Stalder; Laurent Bigler; Susanne Kern; Andreas M. Buser; Norbert V. Heeb (Chemosphere, 2025)

Evolution of chlorinated paraffin and olefin fingerprints in sewage sludge from 1993 to 2020 of a Swiss municipal wastewater treatment plant - Marco C. Knobloch; Jules Hutter; Oscar Mendo Diaz; Markus Zennegg; Jean Claude Vogel; Edith Durisch; Urs Stalder; Laurent Bigler; Susanne Kern; Davide Bleiner; Norbert V. Heeb (Chemosphere, 2024)

Organic carbon burial efficiency in lake sediments controlled by oxygen exposure time and sediment source - Sebastian Sobek; Edith Durisch-Kaiser; Roland Zurbrügg; Nuttakan Wongfun; Martin Wessels; Natacha Pasche; Bernhard Wehrli (Limnology and Oceanography, 2009)
We compared the burial efficiency of organic carbon (buried OC: deposited OC) in a diverse set of 27 different sediments from 11 lakes, focusing on the potential effects of organic matter source, oxygen exposure, and protective sorption of OC onto mineral surfaces. Average OC burial efficiency was high (mean 48%), and it was particularly high in sediments receiving high input of allochthonous organic matter (mean 67%). Further, OC burial efficiency was strongly negatively related to the oxygen exposure time, again particularly so in sediments receiving high allochthonous loads. On the other hand, OC burial efficiency was not related to the mineral surface area, which was used as a proxy of the sorption capacity of the mineral phase for OC. The high OC burial efficiency in many lake sediments can thus be attributed to the frequent and significant input of allochthonous organic matter to lakes, as well as to a strong dependence of OC burial efficiency on oxygen exposure time. This study demonstrates that the carbon sink in lake sediments alters the OC export from the continents to the sea and that the fate of OC in lake sediments (burial vs. mineralization to carbon dioxide and methane) is highly sensitive to environmental conditions.

Sources and emission of greenhouse gases in Danube Delta lakes - Alina Pavel; Edith Durisch-Kaiser; Sorin Balan; Silviu Radan; Sebastian Sobek; Bernhard Wehrli (Environmental Science and Pollution Research, 2009)

Chemical characterization of dissolved organic matter (DOM): A prerequisite for understanding UV-induced changes of DOM absorption properties and bioavailability - Barbara Sulzberger; Edith Durisch-Kaiser (Aquatic Sciences, 2009)

Aerobic and anaerobic methanotrophs in the Black Sea water column - Carsten J. Schubert; Marco J. L. Coolen; Lev N. Neretin; Axel Schippers; Ben Abbas; Edith Durisch‐Kaiser; Bernhard Wehrli; Ellen C. Hopmans; Jaap S. Sinninghe Damsté; Stuart Wakeham; Marcel M. M. Kuypers (Environmental Microbiology, 2006)
Summary Inputs of CH 4 from sediments, including methane seeps on the continental margin and methane‐rich mud volcanoes on the abyssal plain, make the Black Sea the world’s largest surface water reservoir of dissolved methane and drive a high rate of aerobic and anaerobic oxidation of methane in the water column. Here we present the first combined organic geochemical and molecular ecology data on a water column profile of the western Black Sea. We show that aerobic methanotrophs type I are responsible for methane oxidation in the oxic water column and ANME‐1‐ and ANME‐2‐related organisms for anaerobic methane oxidation. The occurrence of methanotrophs type I cells in the anoxic zone suggests that inactive cells settle to deeper waters. Molecular and biomarker results suggest that a clear distinction between the occurrence of ANME‐1‐ and ANME‐2‐related lineages exists, i.e. ANME‐1‐related organisms are responsible for anaerobic methane oxidation below 600 m water depth, whereas ANME‐2‐related organisms are responsible for this process in the anoxic water column above approximately 600 m water depth.

Anaerobic ammonium oxidation in a tropical freshwater system (Lake Tanganyika) - Carsten J. Schubert; Edith Durisch‐Kaiser; Bernhard Wehrli; Bo Thamdrup; Phyllis Lam; Marcel M. M. Kuypers (Environmental Microbiology, 2006)
Summary Here we provide the first direct evidence for the anammox process (anaerobic ammonium oxidation) in a lacustrine system, Lake Tanganyika, the second largest lake in the world. Incubations with 15 N labelled nitrate showed that anammox occurred in the suboxic water layer at 100–110 m water depth. Anammox rates up to 10 nM N 2 h −1 are comparable to those reported for the marine water column. Up to ∼13% of produced N 2 could be attributed to the anammox process whereas the remainder was related to denitrification. Typical lipid biomarkers characteristic of anammox bacteria were found in filtered water from the depths where anammox occurred, thus supporting the presence of anammox bacteria. Further evidence is provided by fluorescence in situ hybridization (FISH), revealing up to 13 000 anammox bacteria cells per ml or 1.4% of all DAPI (4′‐6‐Diamidino‐2‐phenylindole)‐stained cells. Phylogenetic analyses of partial 16S rRNA genes indicated the presence of sequences most closely related to the known anammox bacterium Candidatus ‘Scalindua brodae’ (95.7% similarity). Using the incubation results, a total loss of 0.2 Tg N 2 per year linked to anammox was estimated for the Northern basin of Lake Tanganyika.